Feasibility of flattening filter free beams for hippocampal avoidance whole-brain radiotherapy: a dosimetric and radiobiological analysis - Liu, Fangyu; Peng, Yu; Li, Qian; Zhang, Qianru; Shi, Hongyun; Qie, Shuai; Zhang, Ruohui (Frontiers in Oncology, 2023)
The purpose of this study is to evaluate the potential of the flattening filter free (FFF) mode of a linear accelerator for patients with hippocampal avoidance whole-brain radiotherapy (HA-WBRT) by comparison with flattened beams (FF) technique in the application of volumetric modulated arc therapy (VMAT) and intensity modulated radiation therapy (IMRT) using dosimetric and radiobiological indexes based on the volume of hippocampus and target. 2 VMAT- and 2 IMRT- plans were optimized in Eclipse planning system with 2 different delivery modes (6 MV standard vs. 6 MV FFF) for each of 25 patients. Dose distributions of the target and organs at risk (OARs), normal tissue complication probability (NTCP) of the hippocampus, monitor units, treatment time and quality assurance results were evaluated to compare the normal and FFF beam characteristics by Wilcoxon matched-pair signed-rank test with a significance level of 0.05. VMAT-FFF provided the significantly best homogeneity and conformity of the target, delivered the lowest dose to hippocampus and the other OARs, and led to the lowest NTCP of the hippocampus among all modalities, which has the potential to alleviate neurocognitive decline after WBRT. IMRT-FFF reduced the dose to the lens with similar dose distributions of the target compared with IMRT-FF, whereas the lower dose to the hippocampus was achieved using the conventional beams. The monitor units were obviously increased by 19.2% for VMAT and 33.8% for IMRT, when FFF beams were used. The removal of flattening filter for IMRT resulted in a 26% reduction in treatment time, but VMAT had the similar treatment time for the two modes owing to the limitation of gantry rotation speed. Gamma analysis showed an excellent agreement for all plans at 3%/2 mm, and no statistical differences were found between FF and FFF. In conclusion, this study suggests that FFF mode is feasible and advantageous in HA-WBRT and VMAT-FFF is the optimal solution in terms of dose distribution of the target, OARs sparing, NTCP of the hippocampus and delivery efficiency compared to the other three techniques. Additionally, the advantages of the FFF technique for VMAT are more prominent in cases with small hippocampal volumes.